MINI REVIEW: PEMBUATAN ESI ASAM PEROKSIDA (H2O2) DARI KAWAT TERSALUT AgNPs TERMODIFIKASI KITOSAN - Suriyani, Suriyani; Alimuddin, Alimuddin; Arif, Moh Syaiful (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
This mini-review discusses the development of peroxide acid (H₂O₂) ion-selective electrodes (ISE) from chitosan-modified AgNPs-coated wires. The review highlights the importance of AgNPs in enhancing electrocatalytic activity and conductivity, which are crucial for the development of high-performance electrochemical sensors. Chitosan is used as a stabilizing agent for AgNPs due to its biocompatibility and chemical stability. The coated wire-type ion-selective electrodes are utilized because this method has advantages such as rapid and accurate analysis, high selectivity, no need for separation, a wide measurement range, and low analysis costs. The methodology used in this study involves gathering information from various literature, which is then compiled into detailed case studies. This review aims to integrate information on the modification of AgNPs with chitosan for the development of new ion-selective electrodes (ISE) capable of efficiently detecting H₂O₂. Keywords: H₂O₂, Wire-Coated ISE, AgNPs Modified with Chitosan